Answer:
![t=5.0days](https://tex.z-dn.net/?f=t%3D5.0days)
Step-by-step explanation:
Using the formula for the exponential decay that is
, we have N=
,
and k=0.1374.
Thus,
becomes
![23=46{\times}e^{-0.1374t}](https://tex.z-dn.net/?f=23%3D46%7B%5Ctimes%7De%5E%7B-0.1374t%7D)
![\frac{23}{46}=e^{-0.1374t}](https://tex.z-dn.net/?f=%5Cfrac%7B23%7D%7B46%7D%3De%5E%7B-0.1374t%7D)
![\frac{1}{2}=e^{-0.1374t}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%3De%5E%7B-0.1374t%7D)
Taking log on both sides, we get
![ln(\frac{1}{2})={-0.1374t}](https://tex.z-dn.net/?f=ln%28%5Cfrac%7B1%7D%7B2%7D%29%3D%7B-0.1374t%7D)
![t=\frac{ln\frac{1}{2}}{-0.1}](https://tex.z-dn.net/?f=t%3D%5Cfrac%7Bln%5Cfrac%7B1%7D%7B2%7D%7D%7B-0.1%7D)
![t=\frac{-0.6931}{-0.1374}](https://tex.z-dn.net/?f=t%3D%5Cfrac%7B-0.6931%7D%7B-0.1374%7D)
![t=5.0days](https://tex.z-dn.net/?f=t%3D5.0days)
Solving for y right?
2y = 3x + 4 - x
2y = 2x + 4
y = 2x + 4 over 2
y = 2 (x + 2) over 2
y = x + 2
y - 3 = 2x - 6 over 2
y - 3 = 2(x - 3) over 2
y - 3 = x - 3
y = x
x - y - 2 = 2(2x + 1)
-y - 2 = 2(2x + 1) - x
-y = 2(2x + 1) - x + 2
y = -2(2x + 1) + x - 2
Answer:
x=1/4 , y=-1/4. You can confirm this by substituting the numbers in.
Step-by-step explanation:
The answer is 0.36. I don't think u need to explain why, right ;)
Answer:
6/7
Step-by-step explanation:
x +(-x) =0
5+1= 6
2+5= 7
hopefully that's all correct